Domestic Waste Management Strategy in Batang Bayang River, West Pasaman Regency - Afkar; Nurhasan Syah; Eri Barlian; Nasfryzal Carlo (Jurnal Penelitian Pendidikan IPA, 2025)
Batang Bayang River is one of the rivers that crosses densely populated settlements in Nagari Ujunggading, Lembah Melintang District. Domestic waste from the community, both liquid and solid, is often dumped directly into the river. This causes the condition of the river water quality to worsen due to minimal efforts to manage domestic waste and the habit of people who throw organic and inorganic waste into the river carelessly. The purpose of this study was to analyze river quality against community behavior and then recommend strategies for handling it. The research method used was to analyze test data from the laboratory and determine the level of river pollution using the Pollution Index (IP). To determine community knowledge, attitudes and actions using a questionnaire. The results of the correlation test showed that there was a relationship between knowledge and action with a significance value of 0.001 <0.05, between attitudes towards actions with a significance value of 0.002 <0.05, and between knowledge and attitudes with a significance value of 0.011 <0.05. The handling strategy that can be done by the community is to process waste at home and create a waste bank. The strategy for the government is to provide outreach to the community, create village regulations, create TPS, build domestic IPAL, implement prokasih, cross-sector cooperation and budget priorities in the West Pasaman Regency APBD.